Pola Fungsi Kalimat pada Teks Pidato Capres RI 2024 dalam Berita Daring Detik News sebagai Sumber Bacaan Siswa Kelas 10 SMA - Alya Luthfi Ghani; Dina Handayani Safila Putri; Indri Triani; Mesya Viola Dwi Cahyani; Yaffadevi Palastri Marhaeni Putri; Asep Purwo Yudi Utomo; Tutik Wijayanti (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Everyone must have the ability to speak, especially a leader. When writing speech texts, you are expected to be able to write sentence patterns correctly and understandably. The aim of writing this article is to study the function patterns of sentences in the text of the 2024 RI presidential candidate's speech in the online news Detik News to broaden the insight of researchers and readers, especially as a reading source for grade 10 high school students. This research was conducted so that researchers and readers could compose speech texts and deliver speeches with a correct and appropriate structure. This research uses a pragmatic approach and carries out analysis by identifying sentence patterns in the text of the 2024 Indonesian presidential candidate's speech published in the online news Detik News. Information about the data taken is text that contains the sentence structure of speech texts in Indonesian language learning for class X students. This research uses a qualitative descriptive method and a syntactic method. The data collection technique uses listening and taking note techniques. After researching the text of the 2023 Indonesian presidential candidate's speech on the online news Detik News, various sentence patterns were found. These sentence patterns consist of, among others, single sentence patterns, equivalent compound sentence patterns, multilevel compound sentence patterns, and mixed compound sentence patterns. It is hoped that the results of the analysis from this article will increase students' knowledge in writing and analyzing speech texts well and correctly, and also not only writing and analyzing but also hopefully being able to give public speeches well and of course correctly.